2018
DOI: 10.1088/1742-6596/1136/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

The extended Hubbard model with attractive interactions

Abstract: We discuss the phase diagram of the extended Hubbard model with both attractive and repulsive local and nonlocal interactions. The extended dynamical mean-field theory (EDMFT) and the dual boson method (DB) are compared. The latter contains additional nonlocal correlation effects that are not incorporated in EDMFT. We find that EDMFT and DB give almost identical results in the attractive V regime, where phase separation occurs. This is quite a difference with the previously studied repulsive V regime, where ED… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…For the DFA, these substrate atom are only visible in the corner holes of this idealized model. DFT calculations of the DAS structure [ 16–25 ] show that these first bilayer atoms of the substrate are also significantly shifted and perturbed from their bulk positions, many atoms by 0.3–0.7 Å, [ 24c ] as they bond to the top layer. This makes these so‐called substrate atoms an integral part of the 7 × 7 ad‐layer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the DFA, these substrate atom are only visible in the corner holes of this idealized model. DFT calculations of the DAS structure [ 16–25 ] show that these first bilayer atoms of the substrate are also significantly shifted and perturbed from their bulk positions, many atoms by 0.3–0.7 Å, [ 24c ] as they bond to the top layer. This makes these so‐called substrate atoms an integral part of the 7 × 7 ad‐layer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 59,60 ] Although the details differ, the structural similarities support the idea that strong electron correlations occur for the DFA as proposed theoretically for the 111 surfaces and the DAS structure. [ 13–16 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20]. A rigorous approach to couple these effects necessitates the introduction of a frequency-dependent 'screened' Coulomb interaction in the cluster model, described as 'Extended'-DMFT [21][22][23][24][25][26][27][28][29][30]. This approach is more involved than the comparatively simple one-body embedding of DMFT, but has demonstrated that it can qualitatively describe strongly correlated materials in a fully ab initio approach, including (for example) systems of interest to high-T c superconductivity [31].…”
mentioning
confidence: 99%